EMBRACING THE ISLAMIC PRINCIPLES OF SOCIAL JUSTICE IN THE MALAYSIAN TRADE UNION MOVEMENT (UUM Journal of Legal Studies, 2021)
The notion of social justice in Islam requires fairness in allocating and distributing goods to all members and groups in society. In the context of employment, an employer is required to treat all workers equally and pay their dues suitable with their skills and capabilities. A trade union is an important component under the tripartite system of industrial relations that is imperative in representing workers to demand or improve their working conditions. Although there is legal recognition accorded to trade unions in Malaysia, various state-imposed restrictions have curtailed trade union actions in representing workers for better and equal treatment at the workplace. This paper examined whether the current trade union legal framework in Malaysia is in concord with the Islamic principles of social justice. The objectives of this research are two-fold: first, to examine the principles of social justice in Islam and second, to integrate Islamic principles of social justice into the Malaysian trade union legal framework. In order to fulfil the objectives of this study, it employed the literature research method and referred to Islamic texts (the Quran and hadith). The study has revealed that the restrictive legal system of trade unions in Malaysia contradicts the concept of social justice as embodied in Islamic principles. Therefore, there should be amendments to the legal framework of trade unions in Malaysia to guarantee the exercise of full rights of trade unions in the state and ensure consistency with shariah.